Bicuspid Aortic Valve and Endothelial Dysfunction: Current Evidence and Potential Therapeutic Targets - Antequera-González, Borja; Martínez-Micaelo, Neus; Alegret, Josep M. (Frontiers in Physiology, 2020)
Bicuspid aortic valve (BAV), the most frequent congenital heart malformation, is characterized by the presence of a two leaflets aortic valve instead of a three-leaflets one. BAV disease progression is associated with valvular dysfunction (in form of stenosis or regurgitation) and aortopathy, which can lead to aneurysm and aortic dissection. This morphological abnormality modifies valve dynamics and promotes eccentric blood flow, which gives rise to alterations of the flow pattern and wall shear stress (WSS) of the ascending aorta. Recently, evidence of endothelial dysfunction (ED) in BAV disease has emerged. Different studies have addressed a reduced endothelial functionality by analyzing various molecular biomarkers and cellular parameters in BAV patients. Some authors have found impaired functionality of circulating endothelial progenitors in these patients, associating it with valvular dysfunction and aortic dilation. Others focused on systemic endothelial function by measuring artery flow mediated dilation (FMD), showing a reduced FMD in BAV individuals. Novel biomarkers like increased endothelial microparticles (EMP), which are related to ED, have also been discovered in BAV patients. Finally, latest studies indicate that in BAV, endothelial-to-mesenchymal transition (EndoMT) may also be de-regulated, which could be caused by genetic, hemodynamic alterations or both. Different hypothesis about the pathology of ED in BAV are nowadays being debated. Some authors blamed this impaired functionality just on genetic abnormalities which could lead to a pathological aorta. Nevertheless, thanks to development of new and high-resolution imaging techniques like 4D Flow MRI, hemodynamics have gained great attention. Based on latest studies, alterations in blood flow seem to cause proper modification of the endothelial cells (ECs) function and morphology. It also seems to be associated with aortic dilation and decreased vasodilators expression, like nitric oxide (NO). Although nowadays ED in BAV has been reported by many, it is not clear which its main cause may be. Comprehending the pathways that promote ED and its relevance in BAV could help further understand –and maybe prevent- the serious consequences of this disease. This review will discuss the ED present in BAV, focusing on the latest evidence, biomarkers for ED and potential therapeutic targets (figure 1).